MONOLISA: MEDIA BERBASIS PEMBELAJARAN BERDIFERENSIASI UNTUK MENINGKATKAN DIMENSI BERNALAR KRITIS SISWA SEKOLAH DASAR - Dini Annisa Nurbaety Elsola; Ana Fitrotun Nisa; Heri Maria Zulfiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purposes of this research are (1) create monopoly media for scientific literacy based on differentiated learning to raise elementary school students' critical reasoning dimensions; (2) assess the viability of using monopoly media for science literacy based on differentiated learning to raise elementary school students' critical reasoning dimensions; and (3) assess the efficacy of using monopoly media for science literacy based on differentiated learning to raise elementary school students' critical reasoning dimensions. This research and development using the ADDIE development model. Data collection techniques in this research include questionnaires, interviews, observations, and tests. This research uses qualitative and quantitative descriptive analysis. Based on the results of data analysis, it can be concluded: (1) the final product has elements such as a board game-style media that is intended to be visually appealing, vibrant, and long-lasting; it includes digitally and non-digitally accessible literacy materials; it is based on differentiated learning, which includes a variety of activities and materials, and it is developed to increase students' critical reasoning dimensions; (2) the product feasibility results meet the very feasible category with an average of 97.18%; and (3) effectiveness results show that the scientific literacy monopoly media developed has good effectiveness in improving students' critical reasoning. The percentage of limited trial results obtained by the critical reasoning dimension showed a score of 88.88%. The percentage of extensive trial results shows a score of 90.06%, so there is an increase in results from limited trials and is in the very critical reasoning qualification. The critical reasoning dimension is also supported by the results of a limited trial gain value of 0.62 in the medium category and a broad trial gain value of 0.63 in the medium category.